2023
DOI: 10.22365/jpsych.2023.023
|View full text |Cite
|
Sign up to set email alerts
|

Depression in medical students during the COVID-19 lockdown in Greece

Mariana Styliari,
Michaella Alexandrou,
Georgia Polychronidou
et al.

Abstract: The COVID-19 pandemic has caused a mental health crisis. The purpose of this study was to estimate the prevalence of depression in medical students in Greece during a nationwide lockdown. The secondary aims were to assess the association of depression with socio-demographic factors and students' attitudes regarding the quality of their studies. The data was gathered anonymously through a self-administered online questionnaire between January 11 and 27, 2021. The CES-D scale was used to measure depression rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Additionally, previous research has found an increased prevalence of negative psychological symptoms among healthcare workers ( 44 , 45 ). Owing to the impact of the COVID-19 pandemic, various activities of college students, such as social interactions and physical exercise, have been restricted, which may also increase their tendency toward depression ( 46 , 47 ). Our results also confirm that seniority, profession of medicine and allied health sciences, physical health status, and social interactions are associated with a higher tendency toward depression, which indirectly reflects the impact of the COVID-19 pandemic on depressive tendencies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous research has found an increased prevalence of negative psychological symptoms among healthcare workers ( 44 , 45 ). Owing to the impact of the COVID-19 pandemic, various activities of college students, such as social interactions and physical exercise, have been restricted, which may also increase their tendency toward depression ( 46 , 47 ). Our results also confirm that seniority, profession of medicine and allied health sciences, physical health status, and social interactions are associated with a higher tendency toward depression, which indirectly reflects the impact of the COVID-19 pandemic on depressive tendencies.…”
Section: Discussionmentioning
confidence: 99%